A randomized controlled trial comparing femtosecond laser–assisted cataract surgery versus conventional phacoemulsification surgery. Issue 1 (January 2019) - Roberts, Harry W.; Wagh, Vijay K.; Sullivan, Daniel L.; Hidzheva, Polina; Detesan, Delia I.; Heemraz, Bissoon S.; Sparrow, John M.; O'Brart, David P.S.
Abstract : Purpose : To compare the clinical results of conventional phacoemulsification surgery (CPS) with femtosecond laser–assisted cataract surgery. Setting : Guy's & St Thomas' NHS Foundation Trust, London, United Kingdom. Design : Single‐center prospective randomized interventional case‐controlled trial. Methods : Patients undergoing cataract surgery were randomized to receive either CPS or femtosecond laser–assisted cataract surgery. The surgery was performed with a femtosecond laser (Lensx), and all operations were performed with a gravity‐fluidics torsional phacoemulsification machine (Infiniti). The visual acuity, refraction, central corneal thickness (CCT), central foveal thickness (CFT), endothelial cell loss, and rates of intraoperative and postoperative events were recorded. Quality of life outcomes were measured with the EuroQOL 5 dimensions questionnaire (EQ‐5D) and patient‐reported quality of vision was assessed with a cataract surgery patient‐reported outcome measures questionnaire (Cat‐PROM5). Results : The study comprised 400 eyes of 400 patients who had CPS (n = 200) or femtosecond laser–assisted cataract surgery (n = 200). Seven patients (3.5%) in the femtosecond laser–assisted group were not able to complete the treatment and received CPS. The mean uncorrected distance visual acuity (logarithm of the minimum angle of resolution [logMAR]) 0.15 ± 0.21 (SD) and 0.15 ± 0.19 logMAR after CPS and femtosecond laser–assisted surgery, respectively ( P = 1.0); the pinhole‐corrected visual acuity was 0.04 ± 0.12 and 0.04 ± 0.12, respectively ( P = 1.0); the increase in CCT was 13 ± 19 μm and 15 ± 25 μm, respectively ( P = .5); and the endothelial cell loss was 9.7 ± 13.7 % and 10.2% ± 13.7, respectively ( P = .76). The manifest refraction spherical equivalent error was −0.14 ± 0.60 diopters (D) after CPS and −0.12 ± 0.60 D after femtosecond laser–assisted surgery ( P = .74); the mean change in CFT was 9 ± 35 μm and 6 ± 35 μm, respectively ( P = .55); and the rate of posterior capsule rupture was 3% and 0%, respectively ( P = .03). Conclusions : This study confirms the nonsignificant differences between 2 treatment modalities, notwithstanding a significant reduction in posterior capsule ruptures in the femtosecond laser–assisted surgery group.